Golden Girl - Hilderbrand, Elin (New York, NY : Little, Brown and Company, 2021)
Entering the afterlife due to a hit and run accident, a successful author learns she can observe the earthly lives of her nearly grown children and is also permitted three "nudges" to alter the outcome of events.
Keywords: Women authors -- Death; Fiction; Future life -- Fiction; Spirits -- Fiction; Traffic accident victims -- Fiction; Hit-and-run drivers -- Fiction; Adult children -- Fiction; Mother and child -- Fiction; Family secrets -- Fiction; Secrecy -- Fiction; Nantucket (Mass.) -- Fiction; Domestic fiction